Sorption in 2020s 2020
DOI: 10.5772/intechopen.88621
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Capacities of a Lignin-Based Electrospun Nanofibrous Material for Pharmaceutical Residues Remediation in Water

Abstract: The threat of pharmaceutical residues in natural waters is a pressing concern in both developed and underdeveloped countries. Originating mostly from municipal and farms effluents, pharmaceuticals, poorly eliminated by traditional wastewater treatments enter the environment through sewage treatment plants discharges. Their adsorption on ecological adsorptive materials such as lignin may represent an interesting remediation solution. The present study sets out the sorption capacities and properties of a newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Electrospun lignin nanofibers were characterized by the presence of functional groups, such as ethers, alcohols, and aromatic rings by Camera and colleagues, who found that they removed 70% of the pharmaceuticals pollutant fluoxetine from wastewater (van der Waals forces, electrostatic interactions, – stacking and hydrogen bonds). 231 Chemical crosslinking by glutaraldehyde successfully removed tetracycline, another significant pharmaceutical contaminant, from chitosan combined with PVA nanofibers. A strong adsorption capacity (102 mg g −1 ) was discovered when the various concentrations were adjusted to a volumetric ratio of PVA/chitosan (25 : 75).…”
Section: Environmental Remediation By Using Bio-based Materials By Ad...mentioning
confidence: 99%
“…Electrospun lignin nanofibers were characterized by the presence of functional groups, such as ethers, alcohols, and aromatic rings by Camera and colleagues, who found that they removed 70% of the pharmaceuticals pollutant fluoxetine from wastewater (van der Waals forces, electrostatic interactions, – stacking and hydrogen bonds). 231 Chemical crosslinking by glutaraldehyde successfully removed tetracycline, another significant pharmaceutical contaminant, from chitosan combined with PVA nanofibers. A strong adsorption capacity (102 mg g −1 ) was discovered when the various concentrations were adjusted to a volumetric ratio of PVA/chitosan (25 : 75).…”
Section: Environmental Remediation By Using Bio-based Materials By Ad...mentioning
confidence: 99%